How do you solve 5( u - 1) = 7u + 5- 5( - 2u - 1)?

Mar 9, 2018

$u = - \frac{5}{4}$

Explanation:

$\left(5 u - 1\right) = 7 u + 5 - 5 \left(- 2 u - 1\right)$
$5 u - 5 = 7 u + 5 + 10 u + 5$
$5 u - 5 = 17 u + 10$
$- 15 = 12 u$
$- \frac{15}{12} = u$
$u = - \frac{5}{4}$

Mar 9, 2018

$u = - \frac{5}{4}$

Explanation:

5(u−1)=7u+5−5(−2u−1)    Solve for $u$

1) Clear the parentheses by distributing the $5$ and the $- 5$
After you have distributed, you will get this:
5u−5=7u+5+10u + 5

2) Combine like terms
After you have combined $7 u$ with $10 u$, and $5$ with the other $5$, you will have this:
$5 u - 5 = 17 u + 10$

3) Subtract $5 u$ from both sides to get the $u$ terms together
Once you subtract, you will have this:
$- 5 = 12 u + 10$

4) Subtract $10$ from both sides to isolate the $12 u$ term
$- 15 = 12 u$

5) Divide both sides by $12$ to isolate $u$
$- \frac{15}{12} = u$

6) Reduce the fraction to lowest terms
$- \frac{5}{4} = u$

$u = - \frac{5}{4}$

Check

Sub in $- \frac{5}{4}$ in the place of $u$ in the original equation

This check is not worth the trouble it would take to do it.
You shouldn't waste your valuable time on this check.

If the answer is wrong, so be it.